2011
DOI: 10.1016/j.bbamcr.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-rich protein Hpn from Helicobacter pylori forms amyloid-like fibrils in vitro and inhibits the proliferation of gastric epithelial AGS cells

Abstract: Helicobacter pylori causes various gastric diseases, such as gastritis, peptic ulcerations, gastric cancer and mucosa-associated lymphoid tissue lymphoma. Hpn is a histidine-rich protein abundant in this bacterium and forms oligomers in physiologically relevant conditions. In this present study, Hpn oligomers were found to develop amyloid-like fibrils as confirmed by negative stain transition electron microscopy, thioflavin T and Congo red binding assays. The amyloid-like fibrils of Hpn inhibit the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…3). This behavior confi rmed the earlier fi nding that nickel binding stabilizes the aggregated from of Hpn [11,12]. Notably, HpnA monomers were not transformed to HpnB in the presence of sodium and other cations, indicating that the metal interaction of Hpn is specifi c for nickel.…”
Section: Nickel Binding and Aggregation Of Synthetic Hpnsupporting
confidence: 70%
See 1 more Smart Citation
“…3). This behavior confi rmed the earlier fi nding that nickel binding stabilizes the aggregated from of Hpn [11,12]. Notably, HpnA monomers were not transformed to HpnB in the presence of sodium and other cations, indicating that the metal interaction of Hpn is specifi c for nickel.…”
Section: Nickel Binding and Aggregation Of Synthetic Hpnsupporting
confidence: 70%
“…2 ). The nickel binding capacity of Hpn described earlier [10][11][12] was analyzed by co-incubation of 2 nmol Hpn with nickel agarose at increasing concentrations in phosphate buffered solution with a total volume of 30 μl. After 1 h incubation at 4 °C under shaking conditions, nickel agarose was removed by centrifugation (10 min, 4 °C, 13,000 rpm).…”
Section: Synthesis Structural Integrity and Nickel Binding Of Synthmentioning
confidence: 99%
“…While Hpn and Hpn-2 proteins are certainly central in the nickel trafficking pathways of H. pylori and are possibly directly or indirectly involved in urease activation, their respective roles in these processes remain to be established. Recently, purified Hpn was shown to form in vitro amyloïd-like fibrils that are toxic when applied to cultured gastric epithelial cells (Ge et al, 2011). The existence and function of these fibers and the effect of nickel on their formation has yet to be demonstrated in vivo .…”
Section: In Vivo Urease Activation and Accessory Protein Complexesmentioning
confidence: 99%
“…It is the first time ever that a bacterial amyloid peptide has been found to form pores in the mitochondrial membrane‐based mimics. Previously, we found that Hpn could disrupt the integrity of the mitochondrial membrane through the identification of the depletion of the intracellular ATP levels and the mitochondrial membrane potential . Our experiments involving the Laurdan and Prodan fluorescence indicated that increasing the total protein/lipid ratio leads to a less ordered and more hydrated lipid membrane structure close to the water/lipid interface of lipid bilayers modeling the mitochondrial inner membrane.…”
mentioning
confidence: 62%
“…It is of interest that Aβ(1–42) is also rich in pairs of one specific amino acid, such as one pair each of His, Phe, Ile, Gly, and Val. The formation of amyloid fibrils by Hpn protein was confirmed by transition electron microscopy, and Thioflavin T and Congo red binding assays . The amyloid fibrils of Hpn inhibit the proliferation of gastric epithelial AGS cells through cell cycle arrest and disruption of mitochondrial bioenergetics .…”
mentioning
confidence: 79%